Lithiophilic NiO hexagonal plates decorated Ni collector guiding uniform lithium plating for stable lithium metal anode. Issue 42 (10th October 2019) - Lu, Weiyi; Wu, Chen; Wei, Weifeng; Ma, Jianmin; Chen, Libao; Chen, Yuejiao
Abstract : The Li-plated behavior was modified and Li-dendrites were suppressed through the generation of lithiophilic vertically aligned NiO hexagonal nanoplates on a Ni foil. Abstract : The inevitable formation of dendrite-like morphology restricts the practical application of metallic lithium (Li) in secondary lithium metal batteries (LMBs) though it is regarded as a promising anode material for high-energy-density batteries. Achieving uniform Li plating is an essential strategy to address this issue; nevertheless, it is difficult to realize this on a commercial current collector. Herein, a nanostructured lithiophilic layer of vertically aligned NiO hexagonal nanoplates on Ni foil is formed by a simple hydrothermal strategy. The lithiophilic nature of NiO can effectively guide the homogeneous smooth deposition of metallic Li on Ni collector surface by reducing the nucleation barrier of the electrode. Such a structure of vertical NiO nanoplate arrays transforming into Ni/Li2 O greatly decreases the local current inhomogeneity, facilitates the Li-ion kinetic transfer, and ensures good electron conduction between the lithiophilic layer and the conductive substrate. Benefiting from such a structure, the fabricated anode achieves a steady coulombic efficiency of 97% for 140 cycles (1 mA cm −2 ) and a prolonged lifespan of up to 600 hours (0.25 mA cm −2 ), confirming the effective suppression of volume change and dendrite morphology. This strategy provides an effective and facile way for obtaining a stable lithium metal anode.